2012
DOI: 10.1007/s10506-012-9137-4
|View full text |Cite
|
Sign up to set email alerts
|

Legal stories and the process of proof

Abstract: In this paper, we continue our research on a hybrid narrative-argumentative approach to evidential reasoning in the law by showing the interaction between factual reasoning (providing a proof for 'what happened' in a case) and legal reasoning (making a decision based on the proof). First we extend the hybrid theory by making the connection with reasoning towards legal consequences. We then emphasise the role of legal stories (as opposed to the factual stories of the hybrid theory). Legal stories provide a cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…In a discussion of the anchored narratives theory by Crombag et al (1993), it was shown how argumentative notions were relevant in their scenario analyses (Verheij 2000). Bex has provided a hybrid model connecting arguments and scenarios (Bex 2011;Bex et al 2010), and has worked on the further integration of the two tools (Bex 2015;Bex and Verheij 2013). Connections between arguments and probabilities have been studied by Hepler et al (2007) combining object-oriented modeling and Bayesian networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a discussion of the anchored narratives theory by Crombag et al (1993), it was shown how argumentative notions were relevant in their scenario analyses (Verheij 2000). Bex has provided a hybrid model connecting arguments and scenarios (Bex 2011;Bex et al 2010), and has worked on the further integration of the two tools (Bex 2015;Bex and Verheij 2013). Connections between arguments and probabilities have been studied by Hepler et al (2007) combining object-oriented modeling and Bayesian networks.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, scenario schemes have been used to represent a scenario's completeness (Bex 2011;Bex and Verheij 2013;Verheij et al 2016;Vlek et al 2014Vlek et al , 2016, taking inspiration from the use of scripts in artificial intelligence and cognitive science (Schank and Abelson 1977). Here the cases in a case model are used to represent completeness.…”
Section: Scenariosmentioning
confidence: 99%
“…We have described the process of evidence and credibility assessment in asylum cases as laid out in the EASO guide, and looked at which elements and criteria used in this process are captured by the hybrid theory as presented in the literature (Bex et al 2008(Bex et al , 2011(Bex et al , 2013. Table 1 presents the correspondences between the credibility assessment process and the hybrid theory.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…So, for example, we can say that the general rule "If a witness says p then p is true" can be used to infer con-clusions from witness statements, as in Figure 1. In addition to commonsense reasoning, we can also capture other forms of reasoning using inference rules, such as reasoning with legal rules or reasoning about the legal interpretation or qualification of facts (Bex and Verheij 2013). For example, in the case of Adnan we could say that the facts allow us to infer that there was a serious threat to Adnan's life (Figure 1) by using the rule "If someone lives on the front line of a civil war and their house is hit by grenades, then this counts as a serious threat to their lives".…”
Section: Argumentsmentioning
confidence: 99%
See 1 more Smart Citation